PENINGKATAN KEAKTIFAN SISWA PADA PEMBELAJARAN MATEMATIKA MELALUI SNOWBALL THROWING SISWA SMP - Muhammad Hanifan; Luvy Sylviana Zhanty (Journal on Education, 2019)
The purpose of this research is to increase the activeness of students in mathematics learning for students of SMP Negeri 2 Ngamprah in class VIIIA in the even semester of the 2018/2019 school year through the learning strategy of Snowball Throwing. This research is a class action research consisting of two cycles, each cycle consisting of three stages, namely planning, action and observation, and reflection and evaluation. The data obtained in the form of a percentage increase in activity at the end of the first cycle and at the end of the second cycle. The data analysis technique was conducted using an interactive analysis technique. The results showed an increase in student activity. Increased student activity can be seen from the increasing indicators include: 1) the willingness of students to ask before the action 5.55% and after the action 55.55%, 2) the willingness of students to answer questions before the action 11.11% and after the action 72, 22%, 3) the willingness of students to work on exercises in front of the class before the action 0% and after the action 66.66%, 4) the willingness of students to express opinions before the action 0% and after the action 55.55%. Based on the description above it can be concluded that the application of the Snowball Throwing learning strategy in mathematics learning can increase student activity.